Aktualisasi Mekanisme Investor State Dispute Settlement (ISDS) Dalam Sengketa Joint Venture Investor Asing Dengan Pemerintah Di Indonesia - Syifa Rahmatul Ummah Arif (Pusat Riset dan Inovasi Nasional, 2023)
Foreign investment and business cooperation through joint ventures have emerged as key drivers of Indonesia's economic growth. The increasing influx of foreign investment into Indonesia has, in turn, given rise to disputes between foreign investors and the Indonesian government. Consequently, Indonesia has sought to introduce legal instruments for the resolution of foreign investment disputes. Based on this premise, the author aims to delve deeper into the actualization of the Investor-State Dispute Settlement (ISDS) mechanism in disputes involving foreign investors and the Indonesian government within joint ventures. The examination of the role of the ISDS mechanism in this context is crucial to ensure the protection of investor rights and the provision of legal certainty. The research methodology employed is normative-juridical, utilizing literature review as an approach. The results of this study reveal that investment disputes persist between foreign investors and the Indonesian government due to diverging interests, violations of joint venture agreements, particularly changes in legislation that tend to restrict or disadvantage foreign investors. Consequently, foreign investors often find themselves adversely affected by government policies.